Method for producing ester thiol compound and optical resin containing the same
Using heterogeneous solid acid catalysts simplifies the ester thiols production process, improving efficiency and quality while reducing environmental impact and costs, suitable for optical resin applications.
Patent Information
- Application Number
- JP2024565889
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-01-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-01-25
AI Technical Summary
Existing methods for producing ester thiols require complex purification processes to remove uniform catalysts, leading to high costs, environmental pollution, and potential defects in optical resins due to residual catalysts.
The use of heterogeneous solid acid catalysts, such as super-strong mesoporous materials with sulfonic acid groups, allows for a simpler purification process and efficient reuse of catalysts, reducing wastewater and improving the quality of ester thiols.
This approach enhances manufacturing efficiency and quality of ester thiols, resulting in high-quality optical resins with reduced environmental impact and lower production costs.
Smart Images

Figure 2025502570000001 
Figure 2025502570000002 
Figure 2025502570000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an ester thiol compound, and to a poly(thio)urethane-based polymerizable composition and an optical resin having excellent optical properties, each of which contains an ester thiol compound obtained from the method. [Background technology]
[0002] Polythiourethane-based optical materials have a refractive index similar to that of glass optical materials, and are lighter, more resistant to impact, and more easily dyed than glass optical materials, and are therefore widely used as various optical materials such as eyeglass lenses, camera lenses, etc. In recent years, there has been a demand for optical materials with high functionality such as impact resistance and heat resistance, and there is a demand for high optical transparency, high refractive index, and high Abbe number performance.
[0003] In order to improve the impact resistance of polythiourethane-based optical materials, research on ester thiol compounds has been steadily attempted, and optical material compositions containing ester thiol compounds can be used as photocurable thio-ene compositions and curing agents for epoxy curing systems.
[0004] The ester thiol compound is produced by an esterification method in which a general polyhydric alcohol and a mercaptocarboxylic acid are reacted in the presence of an esterification catalyst while removing by-product water by distillation (see Prior Art Documents 1 to 4).
[0005] However, the conventional method for producing ester thiol compounds requires a special purification process to remove the homogeneous catalyst after the reaction due to the use of a homogeneous catalyst, which may cause additional process costs and environmental pollution due to the generation of a large amount of wastewater.In addition, some of the homogeneous catalyst may remain in the ester thiol compound, which may cause striae, white turbidity, yellowing, etc. when producing optical resins. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Republic of Korea Patent Application 10-2010-7028490 [Patent Document 2] Republic of Korea Patent Application 10-2016-0090624 [Patent Document 3] Republic of Korea Patent Application 10-2017-7035596 [Patent Document 4] Republic of Korea Patent Application 10-2019-0005901 Summary of the Invention [Problem to be solved by the invention]
[0007] Therefore, the present inventors have studied to solve the above-mentioned shortcomings, and have attempted to efficiently produce ester thiol compounds by introducing a solid acid independent of the reaction system to produce ester thiol compounds, thereby converting the more complicated purification process derived from using a homogeneous catalyst into a simple process such as a filter, thereby simplifying the production process. In addition, the catalyst used can be reused to reduce the amount of wastewater and waste generated, making the process economical and environmentally friendly, which is a differentiating point from existing processes. Therefore, the present invention can provide economic benefits in terms of industrialization by reducing process costs, obtaining high yields, and obtaining high-quality products. [Means for solving the problem]
[0008] The above-mentioned object of the present invention is achieved, as one embodiment of the present invention, by a method for producing an ester thiol compound represented by the following formula 3 by reacting a polyhydric alcohol represented by the following formula 1 with a mercaptocarboxylic acid represented by the following formula 2 using a heterogeneous solid acid catalyst.
[0009] [ka] [ka] [ka] [In the above chemical formula, R1 and R2 are each independently H or CH3, l is an integer of 0 to 2, m is an integer of 1 to 4, and n is an integer of 0 to 3.]
[0010] Here, the solid acid catalyst may be natural clay, synthetic silica-alumina, zeolite, ion exchange resin, heteropolyacid, or super strong acid mesoporous material catalyst. The solid acid catalyst is preferably a super strong acid mesoporous material catalyst. In particular, a mesoporous material having sulfonic acid introduced as a super strong acid is more preferable.
[0011] On the other hand, the above-mentioned super strong acid mesoporous material catalyst can be used in a weight ratio of 0.2 to 20, preferably 1 to 20.
[0012] The polyhydric alcohol of the above formula 1 and the mercaptocarboxylic acid of the above formula 2 can be used in a ratio of 20-30:80-70.
[0013] The process of the present invention is preferably carried out in a fixed-bed tubular reactor packed with the above-mentioned heterogeneous solid acid catalyst.
[0014] In another aspect of the present invention, the present invention can provide a polymerizable composition that contains a polyisocyanate together with the ester thiol compound produced by the above-mentioned production method, and may further contain another polythiol or polyol.
[0015] In another aspect of the present invention, the present invention can provide a poly(thiol)urethane composition obtained by polymerizing the polythiol or polyol and polyisocyanate of the above-mentioned polymerizable composition in a reactor so that the molar ratio of SH (or OH) group / NCO group is in the range of 0.5 to 1.5.
[0016] In another aspect, the present invention can provide a resin obtained by curing the poly(thiol)urethane composition, and the resulting resin can be used as an optical material, particularly an optical lens. Effect of the Invention
[0017] The production method of the present invention is capable of improving the production efficiency and quality of ester thiol compounds that are widely used in the chemical, resin, and coating industrial fields, including the optical materials field, and is therefore of great technological and industrial value.
[0018] The ester thiol compound obtained by the production method using a heterogeneous catalyst, which is a feature of the present invention, is economical and can produce high-quality products. Furthermore, by using such a catalyst, optical resins and optical products with excellent quality can be obtained with high economic efficiency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Specific numerical values of the blending ratio (content ratio), physical property values, parameters, etc. described in the present invention can be replaced with the upper limit value (numerical value defined as "not more than" or "less than") or lower limit value (numerical value defined as "not less than" or "exceeding") of the corresponding blending ratio (content ratio), physical property value, parameter, etc. Meanwhile, "%" is based on mass unless otherwise specified.
[0020] Next, the method for producing the ester thiol compound of the present invention will be described in detail.
[0021] First, the present invention aims to easily produce a high-purity ester thiol compound without undergoing an additional complicated purification step by using a heterogeneous catalyst as an ester catalyst used in the production process of an ester thiol compound.
[0022] As described above, the ester thiol compound is produced by an esterification reaction in which mercaptocarboxylic acid is added to polyhydric alcohol in the presence of an ester catalyst while removing water produced as a by-product. There are various types of esterification catalysts, such as Bronsted acids, Lewis acids, or solid acid catalysts. A homogeneous catalyst is mainly used for a normal esterification reaction. Homogeneous catalysts that act in a molecular state are highly active and highly selective because they react in a molecular state. However, since the catalyst exists as a single phase like the reaction system, it is difficult to separate and reuse the product after the reaction is completed, and additional facility operation related to the separation requires a lot of cost. The chemicals and costs required for the separation process can make the process less economical and may even cause environmental pollution. In view of this, the present invention aims to use a heterogeneous solid catalyst that is easy to separate and can be reused. In particular, solid acid catalysts that have developed along with the petrochemical industry are diverse in type and have a wide range of acid strength adjustment, making them highly applicable to the production process of the present invention. Furthermore, if the selectivity can be increased by utilizing the pore structure of a solid catalyst, this will be extremely useful in terms of suppressing the production of by-products and preventing environmental pollution.
[0023] The heterogeneous catalyst that can be used in the production of the ester thiol compound of the present invention is not particularly limited, but representative examples include natural clay, silica-alumina, zeolite, ion exchange resin, heteropolyacid, and superacid mesoporous material. There are amorphous catalysts, but there are also zeolites and mesoporous materials with regular pores. In catalysts with a fixed pore size and shape, shape-selective catalytic action due to the pore structure can also be expected. Zeolite pores are similar in size to normal molecules such as benzene, and using zeolite allows materials to be distinguished according to molecular size. By introducing such properties into catalytic reactions, it is possible to adjust the reaction rate using the size of the reactants or the diffusion rate of the products, or to increase the selectivity for a specific product, which is effective. The size of the pores can also affect the transition state and increase the selectivity for a specific product.
[0024] The above zeolite is a crystalline aluminosilicate, and more than 170 kinds of zeolites with different framework structures can be used, more specifically, MFI, FAU, MOR, BEA, LTA and CHA. The physical and chemical properties of zeolites and their applicability as catalysts are determined by the framework structure, the size of the pore entrance, the shape and size of the pores, the Si / Al molar ratio, the particle size, etc. The framework structure is determined by the type of secondary basic units that form the crystals as a basic matter of zeolites and the method of bonding them. Furthermore, the framework determines the shape and size of the pores, the connection method, and the size of the pore entrance. If there are many large pores, the surface that can contact the reactants is large, and the activity as a catalyst may be high, but the mechanical stability is low. The Si / Al molar ratio, which indicates the degree of aluminum contained in the framework, is related to the generation of acid sites and is also a major factor that determines the hydrothermal stability of zeolites. The size of the particles determines the distance that reactants and products can travel within the zeolite, and small particles have a large outer surface, which makes them highly active in catalytic reactions that must first occur on the outer surface. In addition, the catalytic properties of zeolite, especially its acidity, can be broadly adjusted through a variety of methods, including cation exchange, framework element exchange, support of specific substances, and shielding of acid sites on the outer surface, making it a very useful catalytic material.
[0025] In addition to these functions, it is possible to produce a very effective catalyst by utilizing the fact that the reaction properties change depending on the shape and size of the pores. However, the size of the pore entrance of zeolite is smaller than 0.7 nm, so large molecules cannot enter the pores. Therefore, it cannot be used as a catalyst for organic synthesis reactions of large molecules. Mesoporous materials announced in 1992 have developed mesopores in the range of 3 to 10 nm, which overcomes this limitation. Not only can the size and shape of the pores be widely adjusted depending on the mold material used, but it also has high potential as an acid catalyst because aluminum is introduced into the framework along with silicon. However, unlike zeolites, the pore walls are amorphous, so strong acid sites are not generated, and the pores are very large for the reactants, so it is difficult to expect an increase in selectivity due to the interaction between the pore walls and the reactants. Instead, mesopores of uniform size are regularly developed, the surface area is large, material transfer is fast, and excellent performance as a catalyst can be expected by fixing specific functional groups to the pore walls.
[0026] In particular, the catalyst can be used by introducing a superacid stronger than sulfuric acid into the mesoporous material. Examples of superacids that can be used include sulfonic acid (RSO3H), trifluoromethanesulfonic acid (CF3SO3H), perchloric acid (HClO4), fluoric acid (HF), sulfuric acid derivatives such as chlorosulfuric acid (ClSO3H) and fluorosulfuric acid (FSO3H).
[0027] A preferred superacid is a mesoporous material with sulfonic acid groups (-SO3H) fixed as sulfonic acid, which acts as a heterogeneous catalyst on the surface but acts as a homogeneous catalyst in terms of the active sites. This can be used to create a catalyst. In particular, when sulfonic acid groups are dangling from the surface with organic bond strings, it becomes an effective acid catalyst for organic synthesis reactions. The number of fixed sulfonic acid groups and the surrounding structure determine the number of acid sites and the acid strength, so a solid acid catalyst that meets the purpose can be manufactured. When a silane containing an alkoxy group as well as an -SH functional group is reacted with the surface hydroxyl group of a mesoporous material made of silica, the -SH functional group can be fixed to the pore wall. By treating this with an appropriate oxidizing agent, an acid catalyst with sulfonic acid groups fixed to it can be created. Furthermore, since the synthesis is performed by adding an alkoxysilane or chlorosilane having an -SH functional group or a sulfide bond to the mother liquor of the mesoporous material, acid functional groups can also be fixed to the pore wall during the synthesis process. By fixing Nafion groups, which have extremely strong acid strength, it is possible to fix extremely strong acid sites to the pore walls of mesoporous materials. Unlike zeolites, solid acid catalysts produced in this way are unlikely to exhibit shape selectivity due to their pore structure, but they have a large surface area, fast mass transfer, and are highly active in catalytic reactions of large molecules.
[0028] The polyhydric alcohol of formula (1) used in the method for producing an ester thiol of the present invention is a commercially available substance, and is not particularly limited, and examples thereof include pentaerythritol.
[0029] Examples of the mercaptocarboxylic acid of formula (2) include, but are not limited to, 4-mercaptobutyric acid, 3-mercaptobutyric acid, 3-mercaptopropionic acid, 2-mercaptopropionic acid, 2-mercaptoacetic acid, etc. In this embodiment, or from the viewpoint of the lens polymerization reaction, 3-mercaptopropionic acid and 2-mercaptoacetic acid are preferred.
[0030] The weight ratio of the polyhydric alcohol of the above formula (1) to the mercaptocarboxylic acid of the formula (2) is 10-40:90-60, and a preferred weight ratio is 20-30:80-70.
[0031] Meanwhile, examples of reactors used in the method for producing ester thiol of the present invention include batch reactors and tubular reactors. Among tubular reactors, it is preferable to use a fixed bed tubular reactor that can be filled with the heterogeneous solid acid catalyst of the present invention. In particular, such a catalyst fixed bed reactor can be used by connecting multiple catalyst fixed beds according to the purpose, and has the advantage of a high conversion rate per catalyst weight for the reaction. In addition, such a reactor is easy to produce products that are difficult to handle in a batch reactor, and can be produced continuously, so it has various advantages such as reduced process costs and ease of mass production.
[0032] The temperature of the ester thiol compound production process of the present invention is not particularly limited, but can be 0°C to 250°C, preferably 50°C to 200°C, and more preferably 100°C to 180°C.
[0033] In order to exclude oxygen during the production process of the present invention, it is preferable to carry out the process in a nitrogen or hydrogen atmosphere, and it is also possible to carry out the process in the presence of a solvent or in a state in which the solvent has been removed.
[0034] The solvent used in the present invention is not particularly limited. Examples of the inactivating solvent include aromatic hydrocarbons such as benzene, toluene, and xylene, aliphatic hydrocarbons such as octane and decane, alicyclic hydrocarbons such as cyclohexane, methylcyclohexane, and ethylcyclohexane, halogenated aromatic hydrocarbons such as chlorotoluene, chlorobenzene, dichlorobenzene, dibromobenzene, and trichlorobenzene, nitrogen-containing compounds such as nitrobenzene, N,N-dimethylformamide, N,N-dimethylacetamide, and N,N'-dimethylimidazolidineone, ethers such as dibutyl ether, ethylene glycol dimethyl ether, and ethylene glycol diethyl ether, and amyl formate, n-butyl acetamide, and ethyl acetamide. Examples of the esters include acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, methyl isoamyl acetate, methoxybutyl acetate, 2-ethoxyethyl acetate, sec-hexyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate, cyclohexyl acetate, methylcyclohexyl acetate, benzyl acetate, ethyl propionate, n-butyl propionate, isoamyl propionate, ethyl acetate, butyl stearate, butyl lactate, and amyl lactate, and aromatic carboxylic acid esters such as methyl salicylate, dimethyl phthalate, and methyl benzoate, and can be used alone or in combination of two or more.Preferably, aromatic hydrocarbons are used, and more preferably, toluene, chlorobenzene, and dichlorobenzene.
[0035] The products produced by using the ester thiol compound obtained as above can meet high optical properties, so that they can be used in the production of optical materials, specifically plastic optical lenses.
[0036] According to the present invention, there is provided a polymerizable composition comprising a polythiol / polyol composition comprising the above-described ester thiol compound and an isocyanate composition.
[0037] The polymerizable composition may contain the isocyanate composition and the polyol / polythiol in a mixed state or in a separated state. That is, in the polymerizable composition, the isocyanate composition and the polyol / polythiol may be in a mixed state in contact with each other, or in a separated state so as not to contact each other.
[0038] The polyol component used in the polymerizable composition of the present invention may, for example, be a low molecular weight polyol or a high molecular weight polyol. The above polyols may be used alone or in combination of two or more kinds.
[0039] The low molecular weight polyol is a compound having two or more hydroxyl groups and a number average molecular weight of 60 or more and less than 400. Examples of the low molecular weight polyol include dihydric alcohols such as ethylene glycol, propylene glycol, 1,3-propenediol, 1,4-butylene glycol, 1,3-butylene glycol, 1,2-butylene glycol, 1,5-pentenediol, 1,6-hexenediol, diethylene glycol, triethylene glycol, dipropylene glycol, and mixtures thereof, 1,4-cyclohexenediol, hydrogenated bisphenol A, and bisphenol A, trihydric alcohols such as glycerin, tetrahydric alcohols such as tetramethylolmethane (pentaerythritol), pentahydric alcohols such as xylitol, and hexahydric alcohols such as sorbitol, mannitol, allitol, and iditol.
[0040] The high molecular weight polyol is a compound having two or more hydroxyl groups and a number average molecular weight of 400 or more, for example, 10000 or less, preferably 5000 or less. Examples of the high molecular weight polyol include polyether polyol, polyester polyol, polycarbonate polyol, polyurethane polyol, epoxy polyol, vegetable oil polyol, polyolefin polyol, acrylic polyol, silicone polyol, fluorine polyol, and vinyl monomer modified polyol.
[0041] Examples of the polythiol component used in the polymerizable composition of the present invention, including the ester thiol, include aliphatic polythiols, aromatic polythiols, heterocyclic polythiols, aliphatic polythiols containing sulfur atoms in addition to mercapto groups, aromatic polythiols containing sulfur atoms in addition to mercapto groups, and heterocyclic polythiols containing sulfur atoms in addition to mercapto groups. The thiol may be a thiol oligomer or polythiol, and one or more of them may be used in combination. Specific examples of the thiol include 3,3'-thiobis[2-[(2-mercaptoethyl)thio]-1-propanethiol], bis(2-(2-mercaptoethylthio)-3-mercaptopropyl)sulfide, 4-mercaptomethyl-1,8-dimercapto-3,6-dithiaoctane, 2,3-bis(2-mercaptoethylthio)propane-1-thiol (GST), 2,2-bis(mercaptomethyl)-1,3-propanedithiol, and the like. Thiol, bis(2-mercaptoethyl)sulfide, tetrakis(mercaptomethyl)methane, 2-(2-mercaptoethylthio)propane-1,3-dithiol, 2-(2,3-bis(2-mercaptoethylthio)propylthio)ethanethiol, bis(2,3-dimercaptopropanyl)sulfide, bis(2,3-dimercaptopropanyl)disulfide, 1,2-bis[(2-mercaptoethyl)thio]-3-mer 2-(2-mercaptoethylthio)-3-mercaptopropylthio]ethane, 2-(2-mercaptoethylthio)-3-2-mercapto-3-[3-mercapto-2-(2-mercaptoethylthio)-propylthio]propylthio-propane-1-thiol, 2,2-bis-(3-mercapto-propionyloxymethyl)-butyl ester, 2-(2-mercaptoethylthio)-3-(2- (2-[3-mercapto-2-(2-mercaptoethylthio)-propylthio]ethylthio)ethylthio)propane-1-thiol, (4R,11S)-4,11-bis(mercaptomethyl)-3,6,9,12-tetrathiatetradecane-1,14-dithiol, (S)-3-((R-2,3-dimercaptopropyl)thio)propane-1,2-dithiol, (4R,14R)-4,14-bis(mercaptomethyl)-3,6,9,12,15-Pentathiaheptane-1,17-dithiol, (S)-3-((R-3-mercapto-2-((2-mercaptoethyl)thio)propyl)thio)-2-((2-mercaptoethyl)thio)propane-1-thiol, 3,3'-dithiobis(propane-1,2-dithiol), (7R,11S)-7,11-bis(mercaptomethyl)-3,6,9,12,15-pentathiaheptane Butadecane-1,17-dithiol, (7R,12S)-7,12-bis(mercaptomethyl)-3,6,9,10,13,16-hexathiaoctadecane-1,18-dithiol, 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,8-dimercaptomethyl -1,11-dimercapto-3,6,9-trithiaundecane, pentaerythritol tetrakis(3-mercaptopropionate), trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(2-mercaptoacetate), bispentaerythritol ether hexakis(3-mercaptopropionate), 1,1,3,3-tetrakis(mercaptomethylthio)propane, 1,1,2,2-tetrakis(mercaptomethylthio)ethane, 4,6-bis(mercaptomethylthio)-1,3-dithiane, pentaerythritol tetrakis(2-mercaptoacetate), pentaerythritol tetrakis(3-mercaptopropionate)(PETMP), 2-(2,2-bis(mercaptodimethylthio)ethyl)-1,3-dithiane, etc.,
[0042] As the isocyanate composition used in the polymerizable composition of the present invention, one or more of an alkylene diisocyanate compound, an alicyclic diisocyanate compound, a heterocyclic diisocyanate compound, a sulfur-containing aliphatic diisocyanate compound, and the like can be used.
[0043] The alkylene diisocyanate compounds include, for example, ethylene diisocyanate; trimethylene diisocyanate; tetramethylene diisocyanate; 1,6-hexamethylene diisocyanate; octamethylene diisocyanate; nonamethylene diisocyanate; 2,2-dimethylpentane diisocyanate; 2,2,4-trimethylhexane diisocyanate; decamethylene diisocyanate; butene diisocyanate; 1,3-butadiene-1,4-diisocyanate; 2,4,4-trimethylhexamethylene diisocyanate; 1,6,11-undecane triisocyanate; 1,3,6-hexamethylene triisocyanate; 1,8-diisocyanate-4-isocyanate methyl octane; 2,5,7-trimethyl-1,8-diisocyanate-5-isocyanate methyl octane. bis(isocyanatoethyl)carbonate;bis(isocyanatoethyl)ether;1,4-butylene glycol dipropyl ether-1,2-diisocyanate;1,4-butylene glycol dipropyl ether-1,3-diisocyanate;1,4-butylene glycol dipropyl ether-1,4-diisocyanate;1,4-butylene glycol dipropyl ether-2,3-diisocyanate;1,4-butylene glycol dipropyl ether-2,4-diisocyanate;methyl lysine diisocyanate;lysine triisocyanate;2-isocyanatoethyl-2,6-diisocyanatohexanoate;2-isocyanatopropyl-2,6-diisocyanatohexanoate;mesitylene triisocyanate;2,6-di(isocyanatomethyl)furan, and others.
[0044] Alicyclic diisocyanate compounds include, for example, isophorone diisocyanate; dicyclohexylmethane diisocyanate; 3,8-bis(isocyanatomethyl)tricyclo[5,2,1,0,6]decane; 3,9-bis(isocyanatomethyl)tricyclo[5,2,1,0,6]decane; 4,8-bis(isocyanatomethyl)tricyclo[5,2,1,0,6]decane; 4,9-bis(isocyanatomethyl)tricyclo[5,2,1,0,6]decane; 2,5-bis(isocyanatomethyl)bicyclo[2,2,1]heptane; 2,6-bis(iso Cyanatomethyl)bicyclo[2,2,1]heptane;Bis(isocyanatomethyl)cyclohexane;Dicyclohexylmethane diisocyanate;Cyclohexane diisocyanate;Methylcyclohexane diisocyanate (DIMC);Dicyclohexyldimethylmethane diisocyanate;2,2'-Dimethyldicyclohexylmethane diisocyanate;Bis(4-isocyanato-n-butylidene)pentaerythritol;Dimer acid diisocyanate;2-Isocyanatomethyl-3-(3-isocyanatopropyl)-5-isocyanate 2-Isocyanatomethyl-3-(3-isocyanatopropyl)-6-isocyanatomethyl-bicyclo[2,2,1]-heptane;2-Isocyanatomethyl-2-(3-isocyanatopropyl)-5-isocyanatomethyl-bicyclo[2,2,1]-heptane;2-Isocyanatomethyl-2-(3-isocyanatopropyl)-6-isocyanatomethyl-bicyclo[2,2,1]-heptane;2-Isocyanatomethyl-2-(3-isocyanatopropyl)-6-isocyanatomethyl-bicyclo[2,2,1]-heptane;2-Isocyanatomethyl-3-(3-isocyanatopropyl)-6-(2-isocyanatoethyl) 2-isocyanatomethyl-2-(3-isocyanatopropyl)-5-(2-isocyanatoethyl)-bicyclo[2,2,1]-heptane;2-isocyanatomethyl-2-(3-isocyanatopropyl)-6-(2-isocyanatoethyl)-bicyclo[2,2,1]-heptane;2-isocyanatomethyl-2-(3-isocyanatopropyl)-6-(2-isocyanatoethyl)-bicyclo[2,2,1]-heptane;1,3,5-tris(isocyanatomethyl)-cyclohexane;Dicyclohexylmethane-4,4-diisocyanate (H12MDI) etc.;
[0045] The heterocyclic diisocyanate compounds include, for example, thiophene-2,5-diisocyanate; methylthiophene-2,5-diisocyanate; 1,4-dithiane-2,5-diisocyanate; methyl 1,4-dithiane-2,5-diisocyanate; 1,3-dithiolane-4,5-diisocyanate; methyl 1,3-dithiolane-4,5-diisocyanate; methyl 1,3-dithiolane-2-methyl-4,5-diisocyanate; ethyl 1,3-dithiolane-2,2-diisocyanate; tetrahydrothio These include thiophene-2,5-diisocyanate; methyl tetrahydrothiophene-2,5-diisocyanate; ethyl tetrahydrothiophene-2,5-diisocyanate; methyl tetrahydrothiophene-3,4-diisocyanate; 1,2-diisothiocyanate ethane; 1,3-diisothiocyanate propane; 1,4-diisothiocyanate butane; 1,6-diisothiocyanate hexane; p-phenylenediisopropylidenediisothiocyanate; and cyclohexane diisothiocyanate.
[0046] Examples of sulfur-containing aliphatic diisocyanate compounds include 4-isocyanate-4'-isothiocyanate diphenyl sulfide; 2-isocyanate-2'-isothiocyanate diethyl disulfide; thiodiethyl diisocyanate; thiodipropyl diisocyanate; thiodihexyl diisocyanate; dimethylsulfone diisocyanate; dithiodimethyl diisocyanate; dithiodiethyl diisocyanate; dithiodipropyl diisocyanate; dicyclohexylsulfur-4,4'-diisocyanate; 1-isocyanatemethylthia-2,3-bis(2-isocyanateethylthia)propane, and the like.
[0047] The polymerizable composition may further contain additives such as an internal release agent, an ultraviolet absorber, a near infrared absorber, a polymerization catalyst, a heat stabilizer, a color correction agent, a chain extender, a crosslinking agent, a light stabilizer, an antioxidant, and a filler, if necessary.
[0048] The internal mold release agent may be a component selected from the group consisting of a fluorine-based nonionic surfactant having a perfluoroalkyl group, a hydroxyalkyl group, or a phosphate group; a silicone-based nonionic surfactant having a dimethylpolysiloxane group, a hydroxyalkyl group, or a phosphate group; and an alkyl quaternary ammonium salt, i.e., trimethylcetylammonium salt, trimethylstearyl, dimethylethylcetylammonium salt, triethyldodecylammonium salt, trioctylmethylammonium salt, diethylcyclohexadodecylammonium salt, and an acidic phosphate ester, used alone or in combination of two or more kinds.
[0049] As the ultraviolet absorbing agent, benzophenone-based, benzotriazole-based, triazine-based, salicylate-based, cyanoacrylate-based, oxanilide-based, etc., can be used.
[0050] As the near infrared absorbing agent, azo-based, aminium-based, anthraquinone-based, cyanine-based, polymethine-based, diphenylmethane-based, triphenylmethane-based, quinone-based, diammonium-based, dithiol metal complex-based, squarylium-based, phthalocyanine-based, naphthalocyanine-based, and the like can be used.
[0051] The polymerization catalyst may be an amine, phosphorus, organotin, organocupper, organogallium, organozirconium, organoferric, organozinc, organoaluminum, or organobismuth catalyst. Specifically, tin compounds such as dibutyltin dilaurate, dibutyltin dichloride, dimethyltin dichloride, tetramethyldiacetoxydistannoxane, tetraethyldiacetoxydistannoxane, tetrapropyldiacetoxydistannoxane, and tetrabutyldiacetoxydistannoxane, or amine compounds such as tertiary amines may be used. These may be used alone or in combination of two or more. The amount of catalyst added is preferably in the range of 0.001 to 1% by weight based on the total weight of the monomers in the composition. This range is preferable in terms of not only the polymerizability but also the pot life during operation, the transparency of the obtained resin, and various optical properties or light resistance.
[0052] As the heat stabilizer, metal fatty acid salt-based, phosphorus-based, lead-based, organotin-based, etc. can be used alone or in combination of two or more.
[0053] The resin composition for optical lenses of the present invention may further contain a color correction agent for correcting the initial color of the lens. As the color correction agent, organic dyes, organic pigments, inorganic pigments, etc. may be used. By adding such organic dyes, etc., in an amount of 0.1 to 50,000 ppm, preferably 0.5 to 10,000 ppm per 1 resin composition for optical lenses, it is possible to prevent the lens from becoming yellowish due to the addition of ultraviolet absorbers, optical resins, monomers, etc.
[0054] The present invention also provides a poly(thio)urethane obtained from the above-mentioned polymerizable composition. That is, the poly(thio)urethane may be produced by polymerizing (and curing) the isocyanate composition and thiol in the above-mentioned polymerizable composition. The polymerization reaction may be carried out so that the molar ratio of SH group / NCO group is 0.5 to 1.5, and more preferably 0.9 to 1.1.
[0055] When the composition of the present invention is cured, various molding methods can be used depending on the application, and there is no particular limit to the curing method, but generally, heat curing is mainly used. In this way, the resin of the present invention is obtained. The resin of the present invention is obtained by casting polymerization, which is a common method of mold injection.
[0056] The process of manufacturing eyeglass lenses by thermally curing the resin composition of the present invention is as follows. First, a polymerization initiator is added to the composition of the present invention, and then nitrogen is sprayed to remove air from the inside of the blending tube, followed by stirring under reduced pressure for 1 to 5 hours. After stopping the stirring, the mixture is degassed under reduced pressure and poured into a mold. At this time, the mold is preferably a glass mold or a metal mold fixed with a plastic gasket, or a polyester or polypropylene adhesive tape. The glass mold into which the mixture has been poured is placed in a forced circulation oven, slowly heated from room temperature to 120 to 130°C, held at 120 to 140°C for 1 to 4 hours, slowly cooled to 60 to 80°C, and the solid is released from the mold to obtain an optical lens. The optical lens thus obtained is annealed at a temperature of 120 to 140°C for 1 to 4 hours to obtain the final plastic eyeglass lens (raw material).
[0057] In addition, the optical lens obtained by the above method can be subjected to hard coating and multi-coating treatment to improve optical properties. The hard coating layer is formed by coating a coating composition mainly composed of at least one silane compound having a functional group such as an epoxy group, an alkoxy group, or a vinyl group, and at least one or more metal oxide colloids such as silicic acid oxide, titanium oxide, antimony oxide, tin oxide, tungsten oxide, or aluminum oxide, on the surface of the optical lens to a thickness of 0.5 to 10 mm by impregnation or spin coating, and then curing with heat or ultraviolet light to complete the coating film.
[0058] The multi-coating layer, i.e., the anti-reflective coating layer, can be formed by vacuum deposition or sputtering of metal oxides such as silicon oxide, magnesium fluoride, aluminum oxide, zirconium oxide, titanium oxide, tantalum oxide, and yttrium oxide. Most preferably, silicon oxide and zirconium oxide films are repeatedly vacuum-deposited on both sides of the hard coating film of the lens three or more times, and then the silicon oxide film is vacuum-deposited at the end. Also, if necessary, a water film (fluororesin) layer can be placed at the end, or an ITO layer can be placed between the silicon oxide and zirconium oxide films.
[0059] The optical lens of the present invention can also be used after being colored with a disperse dye or a photochromic dye, if necessary.
[0060] The resin composition for optical lenses of the present invention can be used not only for plastic eyeglass lenses but also for various optical products.
[0061] It is necessary to evaluate whether the optical lens produced according to the present invention has suitable physical properties as a plastic eyeglass lens. The physical properties (1) refractive index and Abbe number (υ), (2) heat resistance (Tg), (3) yellowness index, and (4) striae and opacity were evaluated by the following test methods.
[0062] (1) Refractive index (nE20): The refractive index at 546 nm (E wavelength) was measured at 20° C. using an ABBE refractometer, model DR-M4 from ATAGO. (2) Heat resistance: The glass transition temperature (Tg) of the test piece was measured using a SCINCO DSCN-650 thermal analyzer to determine the heat resistance. (3) Yellowness: The YI value of a 2 mm test piece was measured using a SHIMADZU UV-2600 spectrometer, and the yellowness was compared. (4) Striae and cloudiness: 100 lenses were visually observed, and the occurrence of striae and cloudiness was indicated as follows: 10 or more: ×, 5 to 9: △, 3 to 4: ◯, 2 or less: ◎.
[0063] The present invention is illustrated, but not limited, by the following examples.
[0064] The abbreviations used in the examples have the following meanings:
[0065] TESPT: Bis(tetraethoxysilyl)tetrasulfide TEOS: Tetraethyl orthosilicate CTABr: Cetyltrimethylammonium bromide PETMA: Pentaerythritol tetrathioglycolate TPA: Dodeca tungsto phosphoric acid
[0066] 1. Preparation of superacid mesoporous material catalyst [Synthesis Example 1-1] 5 g of CTABr (0.0137 mol) was dissolved in a solution containing 100 ml of deionized water and 50 ml of 28% ammonium hydroxide (0.55 mol) in a 300 ml Teflon reactor, and then stirred for 15 minutes. 9 g of TEOS (0.038 mol) and 2.59 g of TESPT (0.0096 mol) were further added for 30 minutes and stirred for 2 hours. The Teflon reactor was then placed in an autoclave reactor and aged at 100 °C for 3 days. The solution in which the solid was formed was then filtered and thoroughly washed with deionized water and ethanol. The resulting solid was dried in an oven at 100 °C and calcined at 500 °C.
[0067] 1 g of the obtained solid was dispersed in 50 ml of 35% hydrochloric acid, and then 2 g of bromine (Br2) was added at -10°C for 1 hour and stirred at room temperature for 10 hours. The resulting solid was washed with 100 ml of purified water and then washed again with 200 ml of methanol, and then vacuum dried to obtain a superacid mesoporous material (TESPT-10-MCM) with sulfonic acid introduced therein.
[0068] [Synthesis Examples 1-2 to 1-3] Super strong acid mesoporous materials, TESPT-20-MCM and TESPT-30-MCM, were obtained according to the compositions shown in Table 1 in the same manner as in Synthesis Example 1-1.
[0069] [Table 1]
[0070] 2. Preparation of ester thiol compounds [Synthesis Example 2-1] In a reactor equipped with a Dean-Stock apparatus, a nitrogen gas purge tube, and a thermometer, 100g of pentaerythritol (SAMYANG CHEMICAL CORPORATION, 99%), 5g of the superacid mesoporous material (TESPT-10-MCM) obtained in Synthesis Example 1-1, 300ml of toluene, and 312g of 3-mercaptopropionic acid (ALFA EISAR, 99%) were added, and the temperature inside the reactor was heated to the toluene reflux temperature, and the reaction was carried out for 4 hours while continuously removing the generated water, and then cooled to room temperature. The amount of water removed was 99.0% of the theoretically calculated amount of water.
[0071] The reaction solution was cooled to room temperature, filtered to separate the catalyst, and then concentrated under reduced pressure to obtain 330 g of an ester thiol compound, pentaerythritol tetrakis(3-mercaptopropionate) (hereinafter abbreviated as PETMP). The obtained PETMP was confirmed to be pentaerythritol tetrakis(3-mercaptopropionate) through high performance liquid chromatography and an infrared spectroscope, and had an APHA of 6.
[0072] [Synthesis Examples 2-2 to 2-6, Synthesis Comparative Example 1] PETMP was obtained by the same method as in Synthesis Example 2-1, except that the catalyst shown in Table 2 was used instead of the superacidic mesoporous material (TESPT-10-MCM). The obtained PETMP was confirmed by high performance liquid chromatography and infrared spectroscopy in the same manner as in Synthesis Example 2-1, and the results are shown in Table 2.
[0073] [Synthesis Examples 2-7 to 2-8] In addition to reusing the catalysts used in Synthesis Examples 2-2 and 2-6, PETMP was obtained by producing it in the same manner as in Synthesis Example 1. The results of the obtained PETMP were similar to those of the case using a fresh catalyst.
[0074] [Synthesis Example 2-9] In a reactor equipped with a Dean-Stock apparatus, a nitrogen gas purge tube, and a thermometer, 100g of pentaerythritol, 5g of the superacid mesoporous material (TESPT-20-MCM) obtained in Synthesis Example 1-2, 500ml of toluene, and 271g of mercaptoacetic acid were added, and the temperature inside the reactor was heated to the toluene reflux temperature, and the reaction was carried out for 4 hours while continuously removing the generated water, and then cooled to room temperature. The reaction liquid was cooled to room temperature, filtered to separate the catalyst, and then concentrated under reduced pressure to obtain 312g of pentaerythritol tetrakis(3-mercaptoacetate) (hereinafter abbreviated as PETMA), an ester thiol compound. The obtained PETMA was confirmed via high performance liquid chromatography and an infrared spectroscope in the same manner as in Synthesis Example 2-1, and its APHA was 7.
[0075] [Comparative Synthesis Example 1] In a reactor equipped with a Dean-Stock apparatus, a nitrogen gas purge tube, and a thermometer, 100g of pentaerythritol (SAMYANG CHEMICAL CORPORATION, 99%), 5g of methanesulfonic acid, 300ml of toluene, and 312g of thioglycolic acid (DAICEL, 99%) were added, and the temperature inside the reactor was heated to the toluene reflux temperature, and the reaction was carried out for 4 hours while continuously removing the generated water, and then cooled to room temperature. After this, 246g of a 5% aqueous sodium carbonate solution was added to the obtained reaction product, and the mixture was stirred at 25°C for 1 hour, followed by layer separation to remove the lower layer, and washing twice more with 246g of distilled water. After this, the mixture was heated and concentrated under vacuum to completely remove toluene and traces of water, and then filtered to obtain 337g of PETMP, an ester thiol compound. The color of the obtained ester thiol compound was APHA15.
[0076] [Table 2]
[0077] Using a heterogeneous solid acid catalyst in the production of an ester thiol compound, an ester thiol compound with excellent yield and color can be synthesized, and in particular, it can be confirmed that the amount of wastewater generated is significantly less than that of Comparative Synthesis Example 1 using a homogeneous catalyst. In addition, as in Synthesis Examples 2-7 and 2-8, it was possible to reuse the heterogeneous solid acid catalyst in the production process of the present invention. As a result, the introduction of a heterogeneous solid acid catalyst in the production of an ester thiol compound will make it possible to apply a continuous production method via a catalyst layer instead of the existing batch production method.
[0078] 3. Manufacturing and evaluation of optical lenses [Example 1] 30.8g of 2,3-bis(2-mercaptoethylthio)propane-1-thiol (GST), 19.7g of pentaerythritol tetrakis(3-mercaptopropionate) (PETMP) produced in the above synthesis example, 0.1g of dibutyltin dichloride (DBDC), 0.12g of ZELEC UN, and 1.5g of 2-(2-hydroxy-5-t-octylphenyl)-2H-benzotriazole were added to 46.5g of methylcyclohexane diisocyanate (DIMC), stirred for 10 minutes under a nitrogen stream, vacuum degassed for 1 hour at 1 torr or less, purged with nitrogen, and injected into a glass mold using nitrogen pressure. The glass mold into which the optical resin composition was injected was slowly heated from 30°C to 125°C in a forced circulation oven, held at 125°C for 2 hours, and then cooled to 70°C to remove the optical resin from the mold to obtain a spectacle lens with a center thickness of 1.3 mm. The obtained eyeglass lens was processed to a width of 72 mm, then immersed in an alkaline aqueous cleaning solution and ultrasonically cleaned, and then annealed for 2 hours at 125° C. After this, the lens was dip-coated in a hardening solution and thermally cured, and a multi-coated eyeglass lens was obtained with metal oxide and fluororesin by vacuum deposition.
[0079] [Examples 2 to 8, Comparative Example 1] In addition to using the PETMP shown in Table 3, optical resins were produced in the same manner as in Example 1, and the physical properties were evaluated. The results are shown in Table 3.
[0080] [Table 3]
[0081] The ester thiol compound prepared using the heterogeneous solid acid catalyst in the examples can be used as an optical lens. When comparing Example 2 with Comparative Example 1, the yellowness index was 1.25 and 1.82, showing a very large difference, and the lens using the ester thiol compound prepared using the heterogeneous solid acid catalyst showed a much better result in terms of yellowness than the lens prepared using the homogeneous catalyst.
[0082] In addition, when comparing the Examples and Comparative Examples, the lenses using the ester thiol compounds produced with the heterogeneous solid acid catalyst showed better optical properties such as striae and opacity than those using the homogeneous catalyst, and were therefore usable as optical materials.
Claims
1. A method for producing an ester thiol compound represented by the following formula 3 by reacting a polyhydric alcohol represented by the following formula 1 with a mercaptocarboxylic acid represented by the following formula 2 using a heterogeneous solid acid catalyst. 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】 [In the above chemical formula, R 1 and R 2 are each independently H or CH 3 where l is an integer from 0 to 2, m is an integer from 1 to 4, and n is an integer from 0 to 3.
2. 2. The method according to claim 1, wherein the heterogeneous solid acid catalyst is a natural clay, a synthetic silica-alumina, a zeolite, an ion exchange resin, a heteropolyacid, or a superacid mesoporous material catalyst.
3. The method according to claim 2, wherein the heterogeneous solid acid catalyst is a superacid mesoporous material catalyst.
4. The method according to claim 2, wherein the heterogeneous solid acid catalyst is a mesoporous material having a sulfonic acid introduced therein as a superacid.
5. The method according to claim 3, wherein the superacid mesoporous material catalyst is used in a weight ratio of 0.2 to 20.
6. The method according to any one of claims 1 to 5, characterized in that the polyhydric alcohol of formula 1 and the mercaptocarbonic acid of formula 2 are used in a ratio of 20-30:80-70.
7. The method according to any one of claims 1 to 5, characterized in that it is carried out in a fixed-bed tubular reactor packed with the heterogeneous solid acid catalyst.
8. A polymerizable composition comprising an ester thiol compound produced according to any one of claims 1 to 5 and a polyisocyanate, the polymerizable composition further comprising another polythiol or polyol.
9. The polymerizable composition according to claim 8, wherein the poly(thiol)urethane composition is obtained by polymerizing the polythiol or polyol with a polyisocyanate in a reactor in a molar ratio of SH (or OH) group / NCO group in the range of 0.5 to 1.
5.
10. A resin obtained by curing the poly(thiol)urethane composition according to claim 9.
11. The resin according to claim 10, which is for use as an optical material.
12. The resin according to claim 11, characterized in that the optical material is an optical lens.
Citation Information
Patent Citations
Preparation method of pentaerythritol ester
CN111825579A
Catalyst for synthesizing sulfydryl carboxylic ester compounds as well as preparation method and application of catalyst
CN112169835A
Method for producing ester
JP2005089440A
Polythiol composition for plastic optical lens
JP2019119860A
Decomposition method of lignin, and manufacturing method of aromatic compound
JP2020037065A